Neurobehavioral and metabolic consequences of embryonic triphenyl phosphate exposure across the lifespan in zebrafish - Andrew B. Hawkey; Perry Piatos; Zade R. Holloway; Dilanaz Unal; Jonna Boyda; Richard T. Di Giulio; Edward D. Levin (Neurotoxicology and Teratology, 2026)

Updated inventory and ecological impacts of non-native fish in the Caspian Sea Basin: a systematic review of historical invasion pathways - Azad Teimori; Hamid Reza Esmaeili; Boris Levin; Keyvan Abbasi; Ekaterina D. Vasil’eva (Hydrobiologia, 2026)

Anthropogenic debris accumulation in the Argentine deep sea: evidence of an irreversible sink - Maialen G. Ardusso; Florencia B. Rial; Melisa D. Fernández Severini; Ele Beruschi; Luana Y. Acosta; Andrea N. Álvarez; Juan Cruz Carbajal; Danya Awshah; Xenia Barnes; Lucia Chesta; Moira Décima; Brenda Doti; et al. (Frontiers in Marine Science, 2026)
The seafloor is recognized as a major sink for marine debris, while deep-sea litter remains poorly investigated due to the logistical and economic constraints associated with seabed exploration. This study reports for the first time the occurrence of marine debris found on the Argentine deep seafloor using the SOI’s Remotely Operated Vehicle (ROV), providing the first documented evidence for this region. A total of 29 litter items were recorded across 55.6 km of surveyed seafloor. The highest debris abundance was recorded in submarine canyon areas (1.4 items/km), whereas the Malvinas Basin showed the lowest levels (0.1 items/km), likely associated with hydrodynamic conditions. In addition, plastic items, fishing ropes, and nets were the most frequently recorded types of debris. These findings establish a baseline of the current status of deep-sea marine debris and propose future directions for the region.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Your brain doesn’t look a day past 70! Cross-sectional associations with brain-predicted age in the cognitively-intact oldest-old - Mark K. Britton; Hannah Hoogerwoerd; Joshua Juhasz; Keyanni Joy Johnson; Paul D. Stewart; Pradyumna K. Bharadwaj; Stacy S. Merritt; Cortney J. Jessup; Clinton B. Wright; G. Alex Hishaw; David A. Raichlen; Victor A. Del Bene; et al. (GeroScience, 2025)
The cognitively-intact oldest-old (85 +) may be the most-resilient members of their birth cohort; due to survivorship effects (e.g., depletion of susceptibles), risk factors associated with brain aging biomarkers in younger samples may not generalize to the cognitively-intact oldest-old. We evaluated associations between established aging-related risk factors and brain-predicted age difference (brainPAD) in a cross-sectional cognitively-intact oldest-old sample. Additionally, we evaluated brainPAD-cognition associations to characterize brain maintenance vs. cognitive reserve in our sample. Oldest-old adults (N = 206; 85–99 years; Montreal Cognitive Assessment > 22 or neurologist evaluation) underwent T1-weighted MRI; brainPAD was generated with brainageR, such that more-positive brainPAD reflected more-advanced brain aging. Sex, education, alcohol and smoking history, exercise history, BMI, cardiovascular and metabolic disease history, and anticholinergic medication burden were self-reported. Global cognitive z-score and coefficient of variation were derived from the UDS 3.0 cognitive battery; crystallized-fluid discrepancy was derived from the NIH Toolbox Cognitive Battery. Mean brainPAD was -7.99 (SD: 5.37; range: -24.50, 6.03). Women showed more-delayed brain aging than men (B = -2.9, 95% CI = -4.6, -1.1, p = 0.002). No other exposures were significantly associated with brainPAD. BrainPAD was not associated with any cognitive variable. These findings suggest that cognitively-intact oldest-old adults may be atypically-resistant to risk factors associated with aging in younger samples, consistent with survivorship effects in aging. Furthermore, brainPAD may have limited explanatory value for cognitive performance in cognitively-intact oldest-old adults, potentially due to high cognitive reserve. Overall, our findings highlight the impact of survivorship effects on brain aging research. Graphical Abstract

Persisting neurobehavioral consequences of gestational exposure to cadmium and benzo[a]pyrene in rats - Andrew B. Hawkey; Rongxi Fan; Kala Nwachukwu; Shutong Liu; Anas Gondal; Sarabesh Natarajan; Jade Porter; Melissa Marchese; Giuliana Mesarick; Megan Stout; Corinne Wells; Amir H. Rezvani; et al. (Neurotoxicology and Teratology, 2025)

Pathomorphosis of Parkinson’s Disease on the Background of Stimulation of the Subthalamic Nucleus - E. V. Bril; A. A. Tomskiy; A. A. Gamaleya; A. A. Poddubskaia; D. G. Kesarev; S. M. Omarova; N. V. Fedorova; O. S. Levin (Neuroscience and Behavioral Physiology, 2025)

Deep Fjords Are Excellent Natural Infrastructure for Climate Impact Studies - Anne Gro Vea Salvanes; Natalya D. Gallo; Martine Røysted Solås; Francesco Saltalamacchia; Dag L. Aksnes; Elin Darelius; Svenja Christiansen; Arild Folkvord; Aino Hosia; Stein Kaartvedt; Lisa Levin; Karin Limburg; et al. (Fish and Fisheries, 2025)
Fjords provide valuable research opportunities for marine scientists. They are excellent natural infrastructure for climate impact studies associated with hypoxic episodes and consequences for mesopelagic and deep‐sea ecosystems involving oceanographic circulation processes and basin water renewals. Repeated sampling from the same populations is possible, making fjords excellent systems for developing time series of data for climate impact studies. We provide an overview of the 14 years of data from Norwegian West Coast fjords, focusing on Masfjorden, and report major findings from Oslofjorden in Eastern Norway, exhibiting recurrent hypoxia in the basin waters. We document that the oxygen levels in Masfjorden decreased rapidly by over 60% at 450 m depth in Periphylla periphylla in view of altered optical conditions of the basin water potentially related to deoxygenation. We argue that fjords like Masfjorden and Oslofjorden are not only macrocosms for ecological processes but also are likely an accelerated version of deep oceans with respect to climate impacts.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Neurotoxicology and public health issues of cannabis and cannabinoids - Maxwell C.K. Leung; Edward D. Levin (NeuroToxicology, 2024)

Ecosystem service values support conservation and sustainable land development: Perspectives from four University of California campuses - K. Fausey; M.A. Rippy; G. Pierce; D. Feldman; B. Winfrey; A.S. Mehring; L.A. Levin; P.A. Holden; P.A. Bowler; R. Ambrose (Ecological Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Persisting neurobehavioral consequences of daily or intermittent paternal cannabis administration in F1 and F2 Rats - Andrew B. Hawkey; Sarabesh Natarajan; Olivia Kelly; Anas Gondal; Corinne Wells; Michelle Louise Jones; Amir H. Rezvani; Susan K. Murphy; Edward D. Levin (NeuroToxicology, 2024)

Comparing environmental impacts of deep‐seabed and land‐based mining: A defensible framework - A. Metaxas; C. D. Anglin; A. Cross; J. Drazen; M. Haeckel; G. Mudd; C. R. Smith; S. Smith; P. P. E. Weaver; L. Sonter; D. J. Amon; P. D. Erskine; et al. (Global Change Biology, 2024)
The crises of climate change and biodiversity loss are interlinked and must be addressed jointly. A proposed solution for reducing reliance on fossil fuels, and thus mitigating climate change, is the transition from conventional combustion‐engine to electric vehicles. This transition currently requires additional mineral resources, such as nickel and cobalt used in car batteries, presently obtained from land‐based mines. Most options to meet this demand are associated with some biodiversity loss. One proposal is to mine the deep seabed, a vast, relatively pristine and mostly unexplored region of our planet. Few comparisons of environmental impacts of solely expanding land‐based mining versus extending mining to the deep seabed for the additional resources exist and for biodiversity only qualitative. Here, we present a framework that facilitates a holistic comparison of relative ecosystem impacts by mining, using empirical data from relevant environmental metrics. This framework (Environmental Impact Wheel) includes a suite of physicochemical and biological components, rather than a few selected metrics, surrogates, or proxies. It is modified from the “recovery wheel” presented in the International Standards for the Practice of Ecological Restoration to address impacts rather than recovery. The wheel includes six attributes (physical condition, community composition, structural diversity, ecosystem function, external exchanges and absence of threats). Each has 3–5 sub attributes, in turn measured with several indicators. The framework includes five steps: (1) identifying geographic scope; (2) identifying relevant spatiotemporal scales; (3) selecting relevant indicators for each sub‐attribute; (4) aggregating changes in indicators to scores; and (5) generating Environmental Impact Wheels for targeted comparisons. To move forward comparisons of land‐based with deep seabed mining, thresholds of the indicators that reflect the range in severity of environmental impacts are needed. Indicators should be based on clearly articulated environmental goals, with objectives and targets that are specific, measurable, achievable, relevant, and time bound.

Prenatal and perinatal exposure to Per- and polyfluoroalkyl substances (PFAS)-contaminated drinking water impacts offspring neurobehavior and development - Melissa J. Marchese; Tianyi Zhu; Andrew B. Hawkey; Katherine Wang; Emi Yuan; Jinchen Wen; Sara E. Be; Edward D. Levin; Liping Feng (Science of The Total Environment, 2024)

Embryonic exposures to cadmium and PAHs cause long-term and interacting neurobehavioral effects in zebrafish - Alexandra Stickler; Andrew B. Hawkey; Anas Gondal; Sarabesh Natarajan; Mikayla Mead; Edward D. Levin (Neurotoxicology and Teratology, 2024)

Laboratory measurements of the 15–46 cm wavelength opacity of water vapor under temperature conditions characteristic of the deep atmosphere of Jupiter - Paul G. Steffes; Amadeo Bellotti; Mark D. Sprouse; Kyle G. Phillips; Daniel G. Gerges; Pablo Cembellin; Steven M. Levin; Scott J. Bolton (Icarus, 2023)

Mitochondrial dysfunction and oxidative stress contribute to cross-generational toxicity of benzo(a)pyrene in Danio rerio - Jordan S. Kozal; Nishad Jayasundara; Andrey Massarsky; Casey D. Lindberg; Anthony N. Oliveri; Ellen M. Cooper; Edward D. Levin; Joel N. Meyer; Richard T. Di Giulio (Aquatic Toxicology, 2023)

Triple oxygen isotope compositions of globally distributed soil carbonates record widespread evaporation of soil waters - Julia R. Kelson; Tyler E. Huth; Benjamin H. Passey; Naomi E. Levin; Sierra V. Petersen; Paolo Ballato; Emily J. Beverly; Daniel O. Breecker; Gregory D. Hoke; Adam M. Hudson; Haoyuan Ji; Alexis Licht; et al. (Geochimica et Cosmochimica Acta, 2023)

Embryonic exposure to PFAS causes long-term, compound-specific behavioral alterations in zebrafish - Andrew B. Hawkey; Mikayla Mead; Sarabesh Natarajan; Anas Gondal; Olivia Jarrett; Edward D. Levin (Neurotoxicology and Teratology, 2023)

Developmental exposure of zebrafish to neonicotinoid pesticides: Long-term effects on neurobehavioral function - Andrew B. Hawkey; Dilanaz Unal; Zade R. Holloway; Edward D. Levin (NeuroToxicology, 2023)

Understanding Cancer Screening Intention Among Physically Active Adults Ages 18–49 - A. P. Ewing; M. A. Alalwan; A. L. Best; C. F. Parvanta; E. C. Coughlin; J. M. Dorn; B. L. Levin; C. D. Meade; C. K. Gwede (Journal of Cancer Education, 2023)

Otoliths of marine fishes record evidence of low oxygen, temperature and pH conditions of deep Oxygen Minimum Zones - Leticia Maria Cavole; Karin E. Limburg; Natalya D. Gallo; Anne Gro Vea Salvanes; Arturo Ramírez-Valdez; Lisa A. Levin; Octavio Aburto Oropeza; Andreas Hertwig; Ming-Chang Liu; Kevin D. McKeegan (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Correlation of the regenerative potential of dermal fibroblasts in 2D culture with the biological properties of fibroblast-derived tissue spheroids - Elizaveta V. Koudan; Alla I. Zorina; Aleksandr A. Levin; Frederico D. A. S. Pereira; Stanislav V. Petrov; Saida Sh. Karshieva; Vladimir A. Kasyanov; Natalya E. Manturova; Andrey Yu. Ustyugov; Nikolay N. Potekaev; Vladislav A. Parfenov; Pavel A. Karalkin; et al. (Cell and Tissue Research, 2022)

How much city is too much city? Biodiversity and ecosystem functioning along an urban gradient at the interface of land and sea - Jameal F. Samhouri; Andrew Olaf Shelton; Gregory D. Williams; Blake E. Feist; Shannon M. Hennessey; Krista Bartz; Ryan P. Kelly; James L. O’Donnell; Mindi Sheer; Adrian C. Stier; Phillip S. Levin (Frontiers in Marine Science, 2022)
A huge proportion of the world’s population resides in urban areas along the coast. As cities expand, the ability of coastal ecosystems to provide the benefits people derive from nature, ranging from food from fisheries to coastal defense to maritime transportation and beyond, is in question. While it is well understood that coastal development changes ecosystems, quantitative insights about how terrestrial urbanization fundamentally alters ecosystem structure and function in adjacent freshwater and downstream coastal marine habitats remain rare, though a general expectation is that impacts of terrestrial urbanization will attenuate from land to freshwater to coastal marine habitats. Empirical assessments of these phenomena are especially important for species that rely on freshwater and coastal marine habitats at multiple points in their life cycles, including endangered and threatened Pacific salmon ( Oncorhynchus spp.). We investigated associations between landscape-scale urbanization and ecosystem structure (biodiversity of epibenthic invertebrate taxa) and function (benthic net primary productivity and decomposition) in freshwater and coastal marine habitats across six pairs of more and less urbanized, coastal watersheds in Puget Sound, WA, USA, using principal components analysis, analysis of covariance, and Mantel tests. Greater upland urbanization was associated with greater reductions in freshwater biodiversity, measured as the density and evenness of epibenthic invertebrate families. In contrast and surprisingly, however, coastal marine biodiversity (measured as the density and evenness of epibenthic invertebrate families) tended to be higher at more urbanized sites, suggesting the potential role of low to moderate levels of urbanization-related disturbance in determining coastal marine biodiversity patterns. We found no statistical association between urbanization and freshwater and coastal marine ecosystem functions, estimated from changes in accumulated algal biomass on tiles (benthic net primary productivity) and loss of biomass from litter bags (decomposition). In addition, there was no evidence that changes in ecosystem structure and function with urbanization were more severe in freshwater than coastal marine habitats, as might be expected if the land-sea boundary diminished effects of landscape-scale urbanization. Our results suggest that the effects of urbanization can be complex and that attention to terrestrial, freshwater, and coastal marine systems in concert will produce more effective, ecosystem-based management.

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

Corrigendum: Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)

Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)
Growing human activity in areas beyond national jurisdiction (ABNJ) is driving increasing impacts on the biodiversity of this vast area of the ocean. As a result, the United Nations General Assembly committed to convening a series of intergovernmental conferences (IGCs) to develop an international legally-binding instrument (ILBI) for the conservation and sustainable use of marine biological diversity of ABNJ [the biodiversity beyond national jurisdiction (BBNJ) agreement] under the United Nations Convention on the Law of the Sea. The BBNJ agreement includes consideration of marine genetic resources (MGR) in ABNJ, including how to share benefits and promote marine scientific research whilst building capacity of developing states in science and technology. Three IGCs have been completed to date with the fourth delayed by the Covid pandemic. This delay has allowed a series of informal dialogues to take place between state parties, which have highlighted a number of areas related to MGR and benefit sharing that require technical guidance from ocean experts. These include: guiding principles on the access and use of MGR from ABNJ; the sharing of knowledge arising from research on MGR in ABNJ; and capacity building and technology transfer for developing states. In this paper, we explain what MGR are, the methods required to collect, study and archive them, including data arising from scientific investigation. We also explore the practical requirements of access by developing countries to scientific cruises, including the sharing of data, as well as participation in research and development on shore whilst promoting rather than hindering marine scientific research. We outline existing infrastructure and shared resources that facilitate access, research, development, and benefit sharing of MGR from ABNJ; and discuss existing gaps. We examine international capacity development and technology transfer schemes that might facilitate or complement non-monetary benefit sharing activities. We end the paper by highlighting what the ILBI can achieve in terms of access, utilization, and benefit sharing of MGR and how we might future-proof the BBNJ Agreement with respect to developments in science and technology.

Correction to: Amitifadine, a triple reuptake inhibitor, reduces self-administration of the opiate remifentanil in rats - Edward D. Levin; Corinne Wells; Andrew Hawkey; Zade Holloway; Graham Blair; Alexander Vierling; Ashley Ko; Caroline Pace; John Modarres; Anthony McKinney; Amir H. Rezvani; Jed E. Rose (Psychopharmacology, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Reproductive incompatibility between Amblyomma maculatum (Acari: Ixodidae) group ticks from two disjunct geographical regions within the USA - Michelle E. J. Allerdice; Alyssa N. Snellgrove; Joy A. Hecht; Kris Hartzer; Emma S. Jones; Brad J. Biggerstaff; Shelby L. Ford; Sandor E. Karpathy; Jesus Delgado-de la Mora; David Delgado-de la Mora; Jesus D. Licona-Enriquez; Jerome Goddard; et al. (Experimental and Applied Acarology, 2020)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Blunted cardiac output response to exercise in adolescents born preterm - Kristin Haraldsdottir; Andrew M. Watson; David F. Pegelow; Mari Palta; Laura H. Tetri; Taylor Levin; Melissa D. Brix; Ryan M. Centanni; Kara N. Goss; Marlowe M. Eldridge (European Journal of Applied Physiology, 2020)

Acute pediatric traumatic brain injury severity predicts long-term verbal memory performance through suppression by white matter integrity on diffusion tensor imaging - Hannah M. Lindsey; Sanam J. Lalani; Jonathan Mietchen; Shawn D. Gale; Elisabeth A. Wilde; Jessica Faber; Marianne C. MacLeod; Jill V. Hunter; Zili D. Chu; Mary E. Aitken; Linda Ewing-Cobbs; Harvey S. Levin (Brain Imaging and Behavior, 2020)

FreeSurfer 5.3 versus 6.0: are volumes comparable? A Chronic Effects of Neurotrauma Consortium study - Erin D. Bigler; Marc Skiles; Benjamin S. C. Wade; Tracy J. Abildskov; Nick J. Tustison; Randall S. Scheibel; Mary R. Newsome; Andrew R. Mayer; James R. Stone; Brian A. Taylor; David F. Tate; William C. Walker; et al. (Brain Imaging and Behavior, 2020)

Analysis of Brain Activity Using fMRI Data for Affective Evaluation of the Self and Others - G. G. Knyazev; A. V. Bocharov; A. N. Savostyanov; E. A. Levin; P. D. Rudych (Neuroscience and Behavioral Physiology, 2020)

Effects of sub-chronic methylphenidate on risk-taking and sociability in zebrafish (Danio rerio) - Rebecca G. Brenner; Anthony N. Oliveri; Walter Sinnott-Armstrong; Edward D. Levin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Amitifadine, a triple reuptake inhibitor, reduces self-administration of the opiate remifentanil in rats - Edward D. Levin; Corinne Wells; Andrew Hawkey; Zade Holloway; Graham Blair; Alexander Vierling; Ashley Ko; Caroline Pace; John Modarres; Anthony McKinney; Amir H. Rezvani; Jed E. Rose (Psychopharmacology, 2020)

A preliminary investigation of corpus callosum subregion white matter vulnerability and relation to chronic outcome in boxers - Ashley L. Ware; Elisabeth A. Wilde; Mary R. Newsome; Paolo Moretti; Tracy Abildskov; Gregory S. Vogt; Stephen R. McCauley; Gerri Hanten; Jill V. Hunter; Zili D. Chu; Harvey S. Levin (Brain Imaging and Behavior, 2020)

Opportunities for agent‐based modelling in human dimensions of fisheries - Matthew G. Burgess; Ernesto Carrella; Michael Drexler; Robert L. Axtell; Richard M. Bailey; James R. Watson; Reniel B. Cabral; Michaela Clemence; Christopher Costello; Chris Dorsett; Steven D. Gaines; Emily S. Klein; et al. (Fish and Fisheries, 2020)
Models of human dimensions of fisheries are important to understanding and predicting how fishing industries respond to changes in marine ecosystems and management institutions. Advances in computation have made it possible to construct agent‐based models (ABMs)—which explicitly describe the behaviour of individual people, firms or vessels in order to understand and predict their aggregate behaviours. ABMs are widely used for both academic and applied purposes in many settings including finance, urban planning and the military, but are not yet mainstream in fisheries science and management, despite a growing literature. ABMs are well suited to understanding emergent consequences of fisher interactions, heterogeneity and bounded rationality, especially in complex ecological, social and institutional contexts. For these reasons, we argue that ABMs of human behaviour can contribute significantly to human dimensions of fisheries in three areas: (a) understanding interactions between multiple management institutions; (b) incorporating cognitive and behavioural sciences into fisheries science and practice; and (c) understanding and projecting the social consequences of management institutions. We provide simple examples illustrating the potential for ABMs in each of these areas, using conceptual (“toy”) versions of the POSEIDON model. We argue that salient strategic advances in these areas could pave the way for increased tactical use of ABMs in fishery management settings. We review common ABM development and application challenges, with the aim of providing guidance to beginning ABM developers and users studying human dimensions of fisheries.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

Trophic ecology of a large-bodied marine predator, bluntnose sixgill shark Hexanchus griseus, inferred using stable isotope analysis - Jonathan C. P. Reum; Gregory D. Williams; Chris J. Harvey; Kelly S. Andrews; Phillip S. Levin (Environmental Biology of Fishes, 2020)

Attending to spatial social–ecological sensitivities to improve trade‐off analysis in natural resource management - Daniel K. Okamoto; Melissa R. Poe; Tessa B. Francis; André E. Punt; Phillip S. Levin; Andrew O. Shelton; Derek R. Armitage; Jaclyn S. Cleary; Sherri C. Dressell; Russ Jones; Harvey Kitka; Lynn C. Lee; et al. (Fish and Fisheries, 2020)
Balancing trade‐offs amongst social–ecological objectives is a central aim of natural resource management. However, objectives and resources often have spatial dimensions, which are usually ignored in trade‐off analyses. We examine how simultaneously integrating social–ecological benefits and their spatial complexities can improve trade‐off analysis. We use Pacific herring ( Clupea pallasii, Clupeidae)—an ecologically important forage fish with social, cultural and economic value to communities and commercial fisheries—as a case study. By combining spatial management strategy evaluation with social benefits analysis, we illustrate when policies aimed at aggregate stocks versus spatially segregated substocks of fish fail to balance trade‐offs amongst social–ecological objectives. Spatial measures (e.g. area‐based closures) may achieve some objectives but produce alternative trade‐offs that are sensitive to assumptions about fish population dynamics and social complexities. Our analyses identify policies that are inefficient (e.g. yielding economic costs without producing social or ecological gains), highlight management strategies that generate trade‐offs and indicate when costs are distributed unequally for different user groups. We also point to strategies with outcomes that are robust to spatial uncertainties and reveal research priorities by identifying which performance metrics exhibit sensitivity to spatial ecological assumptions. Collectively, our analyses demonstrate how incorporating social objectives and spatial dynamics into management strategy evaluation can reveal trade‐offs and the implications of management decisions.

Multidisciplinary Observing in the World Ocean’s Oxygen Minimum Zone Regions: From Climate to Fish — The VOICE Initiative - Véronique Garçon; Johannes Karstensen; Artur Palacz; Maciej Telszewski; Tony Aparco Lara; Denise Breitburg; Francisco Chavez; Paulo Coelho; Marcela Cornejo-D’Ottone; Carmen Santos; Björn Fiedler; Natalya D. Gallo; et al. (Frontiers in Marine Science, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Response to L. Witting: PCBs still a major risk for global killer whale populations - Jean‐Pierre Desforges; Ailsa Hall; Bernie McConnell; Aqqalu Rosing Asvid; Jonathan L. Barber; Andrew Brownlow; Sylvain De Guise; Igor Eulaers; Paul D. Jepson; Robert J. Letcher; Milton Levin; Peter S. Ross; et al. (Marine Mammal Science, 2019)

Home sweet suboxic home: remarkable hypoxia tolerance in two demersal fish species in the Gulf of California - Natalya D. Gallo; Lisa A. Levin; Maryanne Beckwith; James P. Barry (Ecology, 2019)

Influence of heme c attachment on heme conformation and potential - Jesse G. Kleingardner; Benjamin D. Levin; Giorgio Zoppellaro; K. Kristoffer Andersson; Sean J. Elliott; Kara L. Bren (JBIC Journal of Biological Inorganic Chemistry, 2018)

Response of Sea Urchin Fitness Traits to Environmental Gradients Across the Southern California Oxygen Minimum Zone - Kirk N. Sato; Andreas J. Andersson; James M. D. Day; Jennifer R. A. Taylor; Michael B. Frank; Jae-Young Jung; Joanna McKittrick; Lisa A. Levin (Frontiers in Marine Science, 2018)

Autoimmune Anti-NMDA Receptor Encephalitis - E. E. Vasenina; O. S. Levin; O. A. Gan’kina; A. Sh. Chimagomedova; D. I. Levikov (Neuroscience and Behavioral Physiology, 2018)

Effects of Ganoderma Lucidum shell-broken spore on oxidative stress of the rabbit urinary bladder using an in vivo model of ischemia/reperfusion - Robert M. Levin; Li Xia; Wu Wei; Catherine Schuler; Robert E. Leggett; Alpha D.-Y. Lin (Molecular and Cellular Biochemistry, 2017)

Differential efficacies of the nicotinic α4β2 desensitizing agents in reducing nicotine self-administration in female rats - Amir H. Rezvani; Susan Slade; Corinne Wells; Venkata M. Yenugonda; Yong Liu; Milton L. Brown; Yingxian Xiao; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2017)

Prevalent and persistent viral infection in cultures of the coral algal endosymbiont Symbiodinium - Karen D. Weynberg; Matthew Neave; Peta L. Clode; Christian R. Voolstra; Christopher Brownlee; Patrick Laffy; Nicole S. Webster; Rachel A. Levin; Elisha M. Wood-Charlson; Madeleine J. H. van Oppen (Coral Reefs, 2017)

Phylogeny and phylogeography of the roaches, genus Rutilus (Cyprinidae), at the Eastern part of its range as inferred from mtDNA analysis - B. A. Levin; E. P. Simonov; O. A. Ermakov; M. A. Levina; E. A. Interesova; O. M. Kovalchuk; Y. A. Malinina; N. S. Mamilov; N. J. Mustafayev; D. V. Pilin; I. V. Pozdeev; N. I. Prostakov; et al. (Hydrobiologia, 2017)

Conceptualization of Social-Ecological Systems of the California Current: An Examination of Interdisciplinary Science Supporting Ecosystem-Based Management - Phillip S. Levin; Sara J. Breslow; Chris J. Harvey; Karma C. Norman; Melissa R. Poe; Gregory D. Williams; Mark L. Plummer (Coastal Management, 2016)

Reduction of nicotine self-administration by chronic nicotine infusion with H1 histamine blockade in female rats - Edward D. Levin; Brandon J. Hall; Autri Chattopadhyay; Susan Slade; Corinne Wells; Amir H. Rezvani; Jed E. Rose (Psychopharmacology, 2016)

A collective navigation hypothesis for homeward migration in anadromous salmonids - Andrew Berdahl; Peter A H Westley; Simon A Levin; Iain D Couzin; Thomas P Quinn (Fish and Fisheries, 2016)
Anadromous salmon (genera O ncorhynchus and S almo ) spend much of their lives feeding in productive northern oceans and then return home to natal sites for reproduction with remarkable accuracy. The mechanisms used for navigation by individuals during migrations are thought to include geomagnetic, celestial and olfactory cues, but rarely are social interactions between individuals considered. Mounting evidence from other taxa indicates that individuals in larger groups can better sense and respond to environmental cues, thus potentially increasing their ability to navigate. Here, we propose that salmon might similarly benefit from collective navigation on their homeward journey. To explore this, we compiled data from multiple studies and found strong evidence that rates of successful homing increase with population abundance, consistent with collective navigation. We then discuss how collective navigation could benefit salmon during each stage of their seaward and homeward migrations, and complement this with a review of salmon sociality. Next, we analyse historic high‐seas catch records and provide new insight into schooling structure of salmon in the marine environment. We argue that collective navigation likely represents a presently under‐appreciated mechanism enhancing the navigational ability of salmon as well as other migratory species, and outline critical tests of our hypothesis.

Role of nicotinic receptors in the lateral habenula in the attenuation of amphetamine-induced prepulse inhibition deficits of the acoustic startle response in rats - José A. Larrauri; Dennis A. Burke; Brandon J. Hall; Edward D. Levin (Psychopharmacology, 2015)

Reproduction of Images Presented at Different Phases of Alpha Waves - F. M. Levin; D. R. Belov; S. F. Kolodyazhnyi (Neuroscience and Behavioral Physiology, 2015)

Impacts of Terrestrial and Shoreline Stressors on Eelgrass in Puget Sound: An Expert Elicitation - Amanda P. Rehr; Gregory D. Williams; Nick Tolimieri; Phillip S. Levin (Coastal Management, 2014)

Multiple Lineages of Avian Malaria Parasites ( Plasmodium ) in the Galapagos Islands and Evidence for Arrival via Migratory Birds - I. I. LEVIN; P. ZWIERS; S. L. DEEM; E. A. GEEST; J. M. HIGASHIGUCHI; T. A. IEZHOVA; G. JIMÉNEZ‐UZCÁTEGUI; D. H. KIM; J. P. MORTON; N. G. PERLUT; R. B. RENFREW; E. H. R. SARI; et al. (Conservation Biology, 2013)
Haemosporidian parasites in the genus Plasmodium were recently detected through molecular screening in the Galapagos Penguin (Spheniscus mendiculus). We summarized results of an archipelago‐wide screen of 3726 endemic birds representing 22 species for Plasmodium spp. through a combination of molecular and microscopy techniques. Three additional Plasmodium lineages were present in Galapagos. Lineage A–infected penguins, Yellow Warblers (Setophaga petechia aureola), and one Medium Ground Finch (Geospiza fortis) was detected at multiple sites in multiple years. The other 3 lineages were each detected at one site and at one time; apparently, they were transient infections of parasites not established on the archipelago. No gametocytes were found in blood smears of infected individuals; thus, endemic Galapagos birds may be dead‐end hosts for these Plasmodium lineages. Determining when and how parasites and pathogens arrive in Galapagos is key to developing conservation strategies to prevent and mitigate the effects of introduced diseases. To assess the potential for Plasmodium parasites to arrive via migratory birds, we analyzed blood samples from 438 North American breeding Bobolinks (Dolichonyx oryzivorus), the only songbird that regularly migrates through Galapagos. Two of the ephemeral Plasmodium lineages (B and C) found in Galapagos birds matched parasite sequences from Bobolinks. Although this is not confirmation that Bobolinks are responsible for introducing these lineages, evidence points to higher potential arrival rates of avian pathogens than previously thought. Linajes Múltiples de Parásitos de Malaria Aviar (Plasmodium) en las Islas Galápagos y Evidencia de su Arribo por Medio de Aves Migratorias

Neurological Complications of Aortocoronary Bypass - N. I. Shrader; V. L. Shaibakova; V. V. Likhvantsev; D. I. Levikov; O. S. Levin (Neuroscience and Behavioral Physiology, 2013)

Autoimmune smoke and fire—coexisting rheumatoid arthritis and chronic obstructive pulmonary disease: a cross-sectional analysis - Vered Bieber; Arnon D. Cohen; Tamar Freud; Nancy Agmon-Levin; Smadar Gertel; Howard Amital (Immunologic Research, 2013)

Effects of chronic sazetidine-A, a selective α4β2 neuronal nicotinic acetylcholine receptors desensitizing agent on pharmacologically-induced impaired attention in rats - Amir H. Rezvani; Marty Cauley; Yingxian Xiao; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2013)

Effects of AZD3480, a neuronal nicotinic acetylcholine receptor agonist, and donepezil on dizocilpine-induced attentional impairment in rats - Amir H. Rezvani; Marty C. Cauley; Edwin C. Johnson; Gregory J. Gatto; Edward D. Levin (Psychopharmacology, 2012)

Diffusion tensor imaging in moderate-to-severe pediatric traumatic brain injury: changes within an 18 month post-injury interval - Elisabeth A. Wilde; Kareem W. Ayoub; Erin D. Bigler; Zili D. Chu; Jill V. Hunter; Trevor C. Wu; Stephen R. McCauley; Harvey S. Levin (Brain Imaging and Behavior, 2012)

Climate shifts the interaction web of a marine plankton community - Tessa B. Francis; Mark D. Scheuerell; Richard D. Brodeur; Phillip S. Levin; James J. Ruzicka; Nick Tolimieri; William T. Peterson (Global Change Biology, 2012)
Climatic effects in the ocean at the community level are poorly described, yet accurate predictions about ecosystem responses to changing environmental conditions rely on understanding biotic responses in a food‐web context to support knowledge about direct biotic responses to the physical environment. Here we conduct time‐series analyses with multivariate autoregressive ( MAR ) models of marine zooplankton abundance in the Northern California Current from 1996 to 2009 to determine the influence of climate variables on zooplankton community interactions. Autoregressive models showed different community interactions during warm vs. cool ocean climate conditions. Negative ecological interactions among zooplankton groups characterized the major warm phase during the time series, whereas during the major cool phase, ocean transport largely structured zooplankton communities. Local environmental conditions (sea temperature) and large‐scale climate indices (El Niño/Southern Oscillation) were associated with changes in zooplankton abundance across the full time series. Secondary environmental correlates of zooplankton abundance varied with ocean climate phase, with most support during the warm phase for upwelling as a covariate, and most support during the cool phase for salinity. Through simultaneous quantitation of community interactions and environmental covariates, we show that marine zooplankton community structure varies with climate, suggesting that predictions about ecosystem responses to future climate scenarios in the Northern California Current should include potential changes to the base of the pelagic food.

Assessing the effects of chronic sazetidine-A delivery on nicotine self-administration in both male and female rats - Joshua E. Johnson; Susan Slade; Corinne Wells; Ann Petro; Hannah Sexton; Amir H. Rezvani; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Yingxian Xiao; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2012)

Food Web Structure and Trophic Control in Central Puget Sound - Chris J. Harvey; Gregory D. Williams; Phillip S. Levin (Estuaries and Coasts, 2012)

Scale and pattern of broadnose sevengill shark Notorynchus cepedianus movement in estuarine embayments - G. D. Williams; K. S. Andrews; S. L. Katz; M. L. Moser; N. Tolimieri; D. A. Farrer; P. S. Levin (Journal of Fish Biology, 2012)
The detailed movements of 32 acoustically tagged broadnose sevengill shark Notorynchus cepedianus were documented in and around north‐east Pacific Ocean estuarine embayments from 2005 to 2007. Arrangements of passive acoustic receivers allowed analysis of movement at several spatial scales, with sex and size examined as possible factors influencing the pattern and timing of these movements. Notorynchus cepedianus exhibited a distinctly seasonal pattern of estuary use over three consecutive years, entering Willapa Bay in the spring, residing therein for extended periods of time during the summer and dispersing into nearshore coastal habitats and over the continental shelf during the autumn. Notorynchus cepedianus within Willapa Bay showed spatio‐temporal patterns of segregation by size and sex, with males and small females using peripheral southern estuary channels early in the season before joining large females, who remained concentrated in central estuary channels for the entire season. Individuals displayed a high degree of fidelity not only to Willapa Bay (63% were documented returning over three consecutive seasons), but also to specific areas within the estuary, showing consistent patterns of site use from year to year. Cross‐estuary movement was common during the summer, with most fish also moving into an adjacent estuarine embayment for some extent of time. Most winter and autumn coastal detections of N. cepedianus were made over the continental shelf near Oregon and Washington, U.S.A., but there were also examples of individuals moving into nearshore coastal habitats further south into California, suggesting the feasibility of broad‐scale coastal movements to known birthing and nursery grounds for the species. These findings contribute to a better understanding of N. cepedianus movement ecology, which can be used to improve the holistic management of this highly mobile apex predator in regional ecosystems.

The α2-adrenergic antagonist idazoxan counteracts prepulse inhibition deficits caused by amphetamine or dizocilpine in rats - José A. Larrauri; Edward D. Levin (Psychopharmacology, 2012)

Comparison of fine-scale acoustic monitoring systems using home range size of a demersal fish - Kelly S. Andrews; Nick Tolimieri; Greg D. Williams; Jameal F. Samhouri; Chris J. Harvey; Phillip S. Levin (Marine Biology, 2011)

Occurrence and biological characteristics of broadnose sevengill sharks (Notorynchus cepedianus) in Pacific Northwest coastal estuaries - Gregory D. Williams; Kelly S. Andrews; Deborah A. Farrer; Gregory G. Bargmann; Phillip S. Levin (Environmental Biology of Fishes, 2011)

Role of individual and developmental differences in voluntary cocaine intake in rats - Nicole L. Schramm-Sapyta; Marty C. Cauley; Dalene K. Stangl; Susan Glowacz; K. Amy Stepp; Edward D. Levin; Cynthia M. Kuhn (Psychopharmacology, 2011)

Sazetidine-A, a selective α4β2 nicotinic acetylcholine receptor ligand: effects on dizocilpine and scopolamine-induced attentional impairments in female Sprague–Dawley rats - Amir H. Rezvani; Marty Cauley; Hannah Sexton; Yingxian Xiao; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2011)

JNJ-39220675, a novel selective histamine H3 receptor antagonist, reduces the abuse-related effects of alcohol in rats - Ruggero Galici; Amir H. Rezvani; Leah Aluisio; Brian Lord; Edward D. Levin; Ian Fraser; Jamin Boggs; Natalie Welty; James R. Shoblock; S. Timothy Motley; Michael A. Letavic; Nicholas I. Carruthers; et al. (Psychopharmacology, 2011)

Phenotypic and genotypic profile of human tympanic membrane derived cultured cells - Sharon L. Redmond; Brett Levin; Kathryn A. Heel; Marcus D. Atlas; Robert J. Marano (Journal of Molecular Histology, 2011)

PPI deficit induced by amphetamine is attenuated by the histamine H1 antagonist pyrilamine, but is exacerbated by the serotonin 5-HT2 antagonist ketanserin - José A. Larrauri; Edward D. Levin (Psychopharmacology, 2010)

The temporal stem in traumatic brain injury: preliminary findings - Erin D. Bigler; Stephen R. McCauley; Trevor C. Wu; Ragini Yallampalli; Sanjeev Shah; Marianne MacLeod; Zili Chu; Jill V. Hunter; Guy L. Clifton; Harvey S. Levin; Elisabeth A. Wilde (Brain Imaging and Behavior, 2010)

Effects of sazetidine-A, a selective α4β2 nicotinic acetylcholine receptor desensitizing agent on alcohol and nicotine self-administration in selectively bred alcohol-preferring (P) rats - Amir H. Rezvani; Susan Slade; Cori Wells; Ann Petro; Lawrence Lumeng; Ting-Kai Li; Yingxian Xiao; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Jed E. Rose; Kenneth J. Kellar; et al. (Psychopharmacology, 2010)

The European carbon balance. Part 1: fossil fuel emissions - P. CIAIS; J. D. PARIS; G. MARLAND; P. PEYLIN; S. L. PIAO; I. LEVIN; T. PREGGER; Y. SCHOLZ; R. FRIEDRICH; L. RIVIER; S. HOUWELLING; E. D. SCHULZE (Global Change Biology, 2010)
We analyzed the magnitude, the trends and the uncertainties of fossil‐fuel CO 2 emissions in the European Union 25 member states (hereafter EU‐25), based on emission inventories from energy‐use statistics. The stability of emissions during the past decade at EU‐25 scale masks decreasing trends in some regions, offset by increasing trends elsewhere. In the recent 4 years, the new Eastern EU‐25 member states have experienced an increase in emissions, reversing after a decade‐long decreasing trend. Mediterranean and Nordic countries have also experienced a strong acceleration in emissions. In Germany, France and United Kingdom, the stability of emissions is due to the decrease in the industry sector, offset by an increase in the transportation sector. When four different inventories models are compared, we show that the between‐models uncertainty is as large as 19% of the mean for EU‐25, and even bigger for individual countries. Accurate accounting for fossil CO 2 emissions depends on a clear understanding of system boundaries, i.e. emitting activities included in the accounting. We found that the largest source of errors between inventories is the use of distinct systems boundaries (e.g. counting or not bunker fuels, cement manufacturing, nonenergy products). Once these inconsistencies are corrected, the between‐models uncertainty can be reduced down to 7% at EU‐25 scale. The uncertainty of emissions at smaller spatial scales than the country scale was analyzed by comparing two emission maps based upon distinct economic and demographic activities. A number of spatial and temporal biases have been found among the two maps, indicating a significant increase in uncertainties when increasing the resolution at scales finer than ≈200 km. At 100 km resolution, for example, the uncertainty of regional emissions is estimated to be 60 g C m −2 yr −1 , up to 50% of the mean. The uncertainty on regional fossil‐fuel CO 2 fluxes to the atmosphere could be reduced by making accurate 14 C measurements in atmospheric CO 2 , and by combining them with transport models.

Incongruent effects of two isolates of Rickettsia conorii on the survival of Rhipicephalus sanguineus ticks - M. L. Levin; L. Killmaster; G. Zemtsova; D. Grant; K. Y. Mumcuoglu; M. E. Eremeeva; G. A. Dasch (Experimental and Applied Acarology, 2009)

Are adolescents more vulnerable to drug addiction than adults? Evidence from animal models - Nicole L. Schramm-Sapyta; Q. David Walker; Joseph M. Caster; Edward D. Levin; Cynthia M. Kuhn (Psychopharmacology, 2009)

Mapping forest patches and scattered trees from SPOT images and testing their ecological importance for woodland birds in a fragmented agricultural landscape - N. Levin; C. McAlpine; S. Phinn; B. Price; D. Pullar; R. P. Kavanagh; B. S. Law (International Journal of Remote Sensing, 2009)

Nicotine effects on learning in zebrafish: the role of dopaminergic systems - Donnie Eddins; Ann Petro; Paul Williams; Daniel T. Cerutti; Edward D. Levin (Psychopharmacology, 2009)

Influence of invasive Spartina growth stages on associated macrofaunal communities - Carlos Neira; Lisa A. Levin; Edwin D. Grosholz; Guillermo Mendoza (Biological Invasions, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Transdermal nicotine attenuates depression symptoms in nonsmokers: a double-blind, placebo-controlled trial - F. Joseph McClernon; F. Berry Hiott; Eric C. Westman; Jed E. Rose; Edward D. Levin (Psychopharmacology, 2006)

Ventral hippocampal α7 and α4β2 nicotinic receptor blockade and clozapine effects on memory in female rats - Ana Pocivavsek; Laura Icenogle; Edward D. Levin (Psychopharmacology, 2006)

Geographical Clustering of Pancreatic Cancers in the Northeast Nile Delta Region of Egypt - A. S. Soliman; X. Wang; J.-D. Stanley; N. El-Ghawalby; M. L. Bondy; F. Ezzat; A. Soultan; M. Abdel-Wahab; O. Fathy; G. Ebidi; N. Abdel-Karim; K.-Anh. Do; et al. (Archives of Environmental Contamination and Toxicology, 2006)

PPARγ and Colon and Rectal Cancer: Associations with Specific Tumor Mutations, Aspirin, Ibuprofen and Insulin-Related Genes (United States) - Martha L. Slattery; Karen Curtin; Roger Wolff; Khe Ni Ma; Carol Sweeney; Maureen Murtaugh; John D. Potter; Theodore R. Levin; Wade Samowitz (Cancer Causes & Control, 2006)

Nicotinic effects on cognitive function: behavioral characterization, pharmacological specification, and anatomic localization - Edward D. Levin; F. Joseph McClernon; Amir H. Rezvani (Psychopharmacology, 2006)

Timing of nicotine effects on learning in zebrafish - Edward D. Levin; Joy Limpuangthip; Tara Rachakonda; Miram Peterson (Psychopharmacology, 2006)

Kinesthetic, but not visual, motor imagery modulates corticomotor excitability - Cathy M. Stinear; Winston D. Byblow; Maarten Steyvers; Oron Levin; Stephan P. Swinnen (Experimental Brain Research, 2006)

Nicotinic–serotonergic drug interactions and attentional performance in rats - Amir H. Rezvani; D. Patrick Caldwell; Edward D. Levin (Psychopharmacology, 2005)

Nectin-1/HveC Mediates herpes simplex virus type-1 entry into primary human sensory neurons and fibroblasts - Scott A Simpson; Michael D Manchak; Elizabeth J Hager; Claude Krummenacher; J Charles Whitbeck; Myron J Levin; Curt R Freed; Christine L Wilcox; Gary H Cohen; Roselyn J Eisenberg; Lewis I. Pizer (Journal of NeuroVirology, 2005)

Chronic transdermal nicotine patch treatment effects on cognitive performance in age-associated memory impairment - Heidi K. White; Edward D. Levin (Psychopharmacology, 2004)

Family history and colorectal cancer: predictors of risk - M.L. Slattery; T.R. Levin; K. Ma; D. Goldgar; R. Holubkov; S. Edwards (Cancer Causes & Control, 2003)

Adolescent-onset nicotine self-administration modeled in female rats - Edward D. Levin; Amir H. Rezvani; Daniel Montoya; Jed E. Rose; H. Scott Swartzwelder (Psychopharmacology, 2003)

Multi-functional T-DNA/Ds tomato lines designed for gene cloning and molecular and physical dissection of the tomato genome - D. Gidoni; E. Fuss; A. Burbidge; G-J. Speckmann; S. James; D. Nijkamp; A. Mett; J. Feiler; M. Smoker; M.J. de Vroomen; D. Leader; T. Liharska; et al. (Plant Molecular Biology, 2003)

Identification of molecular markers associated with leptine in reciprocal backcross families of diploid potato - T. Medina; E. Fogelman; E. Chani; A. Miller; I. Levin; D. Levy; R. Veilleux (Theoretical and Applied Genetics, 2002)

Ovariectomy of young mutant amyloid precursor protein transgenic mice leads to increased mortality - Justine A. Levin-Allerhand; Jonathan D. Smith (Journal of Molecular Neuroscience, 2002)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Identification, transcription and sequence analysis of the Spodoptera littoralis nucleopolyhedrovirus (SpliNPV) DNA polymerase gene - J. Huang; D. B. Levin (Archives of Virology, 2001)

Abstracts of Presentations at the 21st congress of the Israeli phytopathological society February 14–15, 2000 ARO, the Volcani Center, Bet Dagan, Israel - S. Droby; G. Kritzman; A. Gamliel; Miriam Austerweil; Yael Skutelski; I. Peretz-Alon; E. Becker; J. Katan; R. Cohen; M. Edelstein; Carmela Horev; Y. Burger; et al. (Phytoparasitica, 2000)

Halo formation as a characteristic of leukocyte functional activity - M. Z. Fedorova; V. N. Levin; V. D. Goricheva; O. N. Semenova (Bulletin of Experimental Biology and Medicine, 2000)

Uncertainty Analysis of Regional Mercury Exposure - C. Seigneur; K. Lohman; P. Pai; K. Heim; D. Mitchell; L. Levin (Water, Air, & Soil Pollution, 1999)

Characterization of Spodoptera littoralis type B nucleopolyhedrovirus infection in selected insect cell lines - J. Huang; X. Liu; D. B. Levin (Archives of Virology, 1999)

Four-week nicotine skin patch treatment effects on cognitive performance in Alzheimer's disease - Heidi K. White; E. D. Levin (Psychopharmacology, 1999)

Transdermal nicotine effects on attention - E. D. Levin; C. Keith Conners; Donna Silva; Sean C. Hinton; Warren H. Meck; John March; Jed E. Rose (Psychopharmacology, 1998)

Mixing Ratios and Photostationary State of NO and NO2 Observed During the POPCORN Field Campaign at a Rural Site in Germany - F. Rohrer; D. Brüning; E. S. Grobler; M. Weber; D. H. Ehhalt; R. Neubert; W. Schüßler; I. Levin (Journal of Atmospheric Chemistry, 1998)

Nicotinic acetylcholine involvement in cognitive function in animals - E. D. Levin; Barbara B. Simon (Psychopharmacology, 1998)

Identification and characterization of the Spodoptera littoralis nucleopolyhedrovirus type B lef-3 gene - J.-L. C. Wolff; L. M. Herzog; L. Sun; D. B. Levin (Archives of Virology, 1998)

Probabilistic assessment of regional mercury exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Probabilistic Assessment of Regional Mercury Exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Serologically defined linear epitopes in the E2 envelope glycoprotein of Semliki Forest virus - N. Ariel; S. Lehrer; E. Elhanaty; T. Sabo; P. Brodt; B. Lachmi; D. Katz; R. Levin; H. Grosfeld; B. Velan; A. Shafferman (Archives of Virology, 1990)

Delayed spatial alternation deficits resulting from perinatal PCB exposure in monkeys - Edward D. Levin; Susan L. Schantz; Robert E. Bowman (Archives of Toxicology, 1988)